The rise of the Kremlin Troll / Sarah Morrison - Morrison, Sarah (Centre For Media And Information Warfare Studies, 2021)
After the Cold War collapse, the Russian government demonstrated several failings regarding military strategy and information operations. The Russian government then undertook improvements through critical learnings to formulate information warfare and adapt to online communication applications. Included in this strategy was the flooding of communications with a narrative designed to confuse and cast doubt on Russian and world events. This paper examines Russia's approach to information warfare during the Chechnya Wars, the Georgia war, the 2010/2011 Arab Spring protests, and the international protests and internal unrest in Russia at the end of 2011. As demonstrated through this timeline, rather than failing at information operations, Russia has been learning and adapting these techniques and strategies using online communication applications, particularly social medial networks (SMNs), resulting in the rise of the Kremlin troll. This paper will conclude by examining the Internet Research Agency (IRA), a known Russian troll farm in St Petersburg.